Performing Against Annihilation Identity and Consciousness in J.R.R. Tolkien, Richard Wagner and George R.R. Martin - Schepp, Lukas (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
XII, 327 p. 82 illus., 61 illus. in color.